At Risk of Deprivation - Bergmann, Jonas (Springer Nature, 2023)
This open access book examines how and why various forms of climate (im)mobilities can impact people's objective and subjective well-being. Worsening climate impacts are forcing subsistence farmers worldwide to decide between staying or leaving their homes. This mixed methods study analyzes cases of climate-related migration, displacement, relocation, and immobility in Peru's coastal, highland, and rainforest regions. The results reveal that numerous farmers experienced profound and often negative well-being impacts, regardless of whether they stayed or migrated. The higher the structural constraints, such as weak governance, and the more damaging the climate impacts were, the higher the risk of well-being declines. Additionally, the affected individuals often had limited agency and ability to mitigate losses. These findings challenge the notion of "migration as adaptation" and emphasize the importance of safeguarding the human rights and security of those affected while addressing loss and damage. Without significant investments in such efforts, climate impacts could sharply diminish the well-being of numerous subsistence farmers worldwide—irrespective of whether they stay or migrate.